Apocalyptic Letter Writing in Early Christianity: The Letter of Lyon and Vienne and its Reception of the Apocalypse of John - Dik, John (Zeitschrift für antikes Christentum, 2025)
The letter of Lyon has attracted both researchers of the history of early Christianity because it gives many insights on the rise of Christian communities in the Roman province of Gaul and researchers of biblical studies because it is deeply embedded in biblical language and testifies to the spread of New Testament writings to the West of the Empire as early as the second century A.D. In the present study, I focus on the reception of John’s Apocalypse as we find it in the Letter of Lyon by firstly analyzing the forms of the letters and showing their socio-historical implications for the networks among Christian communities in the second century A.D. and secondly how the Letter of Lyon references and alludes to specific texts and motifs of John’s Apocalypse. Thereby, I draw conclusions on the Apocalypse’s relevance for the church in the second century and argue that both the Apocalypse of John and the Letter of Lyon could be classified as apocalyptic letters .